Posterior Reversible Encephalopathy Syndrome in Chronic Kidney Disease: Incidence, Outcomes, and Risk Factors in a National Cohort - Mingyue He; Avrum Gillespie (Kidney Medicine)
Rationale & Objective: Posterior reversible encephalopathy syndrome (PRES) is an acute neurological condition that, if untreated, can result in severe complications, such as intracerebral hemorrhage. Patients with chronic kidney disease (CKD) are at an increased risk of developing PRES; however, it is unclear whether this risk is primarily driven by comorbid conditions or if renal dysfunction itself is an independent risk factor. This study aimed to evaluate the incidence, outcomes, and resource utilization of PRES across CKD stages compared with patients without kidney disease. Study Design: A retrospective study using the Nationwide Inpatient Sample Database. Setting & Participants: Adult patients nonelectively admitted with PRES from 2016 to 2019. Exposures: Different stages of CKD versus no kidney disease Outcomes: All-cause in-hospital mortality, Incidence of PRES hospitalizations, in-hospital morbidity (intracerebral hemorrhage, ischemic stroke, brain herniation, and status epilepticus), and health care resource utilization (length of hospital stay and total hospitalization charges) Analytical Approach: Multivariate logistic and linear regression analyses were conducted using survey design methods. Results: The cohort included 12,605 patients, representing 0.014% of all admissions. PRES incidence increased from 0.013% in 2016 to 0.015% in 2019 (P = 0.01) and demonstrated a dose-response relationship with CKD stage progression. Key risk factors for PRES included female sex, White race, hypertension, metastatic cancer, solid organ transplantation, rheumatologic disorders, substance use disorders, carotid artery stenosis, migraines, and cerebral atherosclerosis. Kidney failure (KF) was strongly associated with in-hospital mortality (aOR 5.12, 95% CI, 2.09-12.53, P < 0.001). The length of stay, total hospitalization charge, and rates of neurological complications were similar between CKD/KF and patients without kidney disease. Limitations: The use of administrative data limits access to detailed clinical information. Residual confounding factors remain possible. Conclusions: This is the largest study to date on PRES in CKD populations. CKD is strongly associated with PRES, with a dose-response relationship, and KF is an independent risk factor for in-hospital mortality, emphasizing the need for heightened clinical vigilance in this population. Plain-Language Summary: Posterior Reversible Encephalopathy Syndrome (PRES) is a serious brain condition that can cause seizures, confusion, and even death if not recognized and treated in time. However, it is often overlooked because its symptoms can be vague. While PRES is commonly linked to high blood pressure and immune system diseases, its connection to chronic kidney disease (CKD) has been unclear. This study used a large national database to examine how often PRES occurs in people with CKD and its impact on their health. The findings show that the risk of PRES increases as kidney disease worsens, with patients in kidney failure being the most vulnerable. These results highlight the need for early recognition and close monitoring of patients with CKD to improve their care.